The moderation effect of social factors on marketing factors in consumer research. Issue 2 (3rd April 2019) - Wu, Xiaochuang; Chen, Helen X.; Li, Xiaohong
Abstract: Consumer research tends to isolate the impact of marketing and social factors. Little has been done to include both. This paper aimed to find out what would happen when these two sets of factors are included. Two models were built in this paper, Model I with the marketing factors only and Model II with both the marketing and social factors. Data was collected in Ireland among more than 1473 transition year students in a personal survey regarding their willingness to learn Chinese. Data were analysed by using structural equation modelling (SEM). Results showed the two social variables, acculturation and intergenerational influence, significantly consolidated the effects of brand awareness on both brand trust and purchase behaviour; and they diminished the impact of brand trust on purchase behaviour. Empirical evidence suggested the worthiness for marketing researchers to examine both marketing and social factors in consumer research.